2012
DOI: 10.1007/s00726-012-1306-y
|View full text |Cite
|
Sign up to set email alerts
|

Modafinil improves performance in the multiple T-Maze and modifies GluR1, GluR2, D2 and NR1 receptor complex levels in the C57BL/6J mouse

Abstract: Modafinil has been shown to modify behavioural and cognitive functions and to effect several brain receptors. Effects, however, were not observed at the receptor protein complex level and it was therefore the aim of the study to train mice in the multiple T-Maze (MTM) as a paradigm for spatial memory and to determine paralleling brain receptor complex levels. Sixty C57BL/6J mice were used in the study and divided into four groups (trained drug injected; trained vehicle injected; yoked drug injected; yoked vehi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 46 publications
0
14
1
Order By: Relevance
“…More recently, modafinil increased extracellular glutamate in the nucleus accumbens of cocaine experienced rats (Mahler et al, 2012). Modafinil does not bind to GluN receptors (Nguyen et al), but does modify NMDA receptor complexes in the hippocampus of mice as indicated by an increase in GLuN1 complexes (Sase et al, 2012). We found no meth or modafinil induced differences in receptor expression in the hippocampus following the OIP place task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, modafinil increased extracellular glutamate in the nucleus accumbens of cocaine experienced rats (Mahler et al, 2012). Modafinil does not bind to GluN receptors (Nguyen et al), but does modify NMDA receptor complexes in the hippocampus of mice as indicated by an increase in GLuN1 complexes (Sase et al, 2012). We found no meth or modafinil induced differences in receptor expression in the hippocampus following the OIP place task.…”
Section: Discussionmentioning
confidence: 99%
“…Modafinil does not directly bind to GluN receptors (Nguyen et al, 2011), but does modify GluN receptor complexes (Sase et al, 2012). Thus, we also determined whether modafinil would affect the expression of GluN receptors in the prefrontal cortex, perirhinal cortex, and hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…30 Modafinil also increases receptor complex levels of several AMPA subtypes in mice. 31 Given that modafinil was effective in a patient with FRRS1L haploinsufficiency, this may suggest a link between FRRS1L, AMPA, and fatigue symptoms in 9q31.2q32 deletions.…”
Section: Methodsmentioning
confidence: 99%
“…These receptors mediate ion transport in the cellular membrane and are considered potential drug targets for treatment of a number of neurological diseases including Alzheimer's and Parkinson's (1)(2)(3)(4)(5)(6). The NMDAR is unique among the glutamate receptors in that it forms hetero-tetrameric complexes using two glycine-binding GluN1 subunits, and two other subunits, either the glutamate-binding subunit GluN2 or the glycine-binding GluN3 subunit (7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%